2004
DOI: 10.1577/h03-068.1
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyophoniasis: An Emerging Disease of Chinook Salmon in the Yukon River

Abstract: Before 1985, Ichthyophonus was unreported among Pacific salmon Oncorhynchus spp. from the Yukon River; now it infects more than 40% of returning adult Chinook salmon O. tshawytscha. Overall infection prevalence reached about 45% in the Yukon River and about 30% in the Tanana River between 1999 and 2003. Mean infection prevalence was greater in females than males in the main-stem Yukon River during each of the 5 years of the study, but the infection prevalence in males increased each year until the difference w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 22 publications
4
108
0
Order By: Relevance
“…Prevalence of infection was 12.5%, mostly infected tissues of the gas bladder with I.hoferi macroscopically had white nodules mainly near blood vessels with various degrees of congestion different from neighboring transparent portions of the same specimen and this may be attributed to the relatively more affection of highly vascularised organs which identify Icthyophonus systemic nature (Spanggaard, et al 1994 andEl-Khattib andElyas, 2003). Growth of nonseptated microhyphae and tubular club shaped macrohyphae resembled that of Kocan et al (2004). The recorded histopathological changes in gas bladder of naturally infected O.niloticus were sloughing in the epithelial layer, subepithelial edema with mononuclear cells infiltration in the submucosa and congestion in the blood vessels of the submucosa with eosinophilic granular cells infiltrations.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Prevalence of infection was 12.5%, mostly infected tissues of the gas bladder with I.hoferi macroscopically had white nodules mainly near blood vessels with various degrees of congestion different from neighboring transparent portions of the same specimen and this may be attributed to the relatively more affection of highly vascularised organs which identify Icthyophonus systemic nature (Spanggaard, et al 1994 andEl-Khattib andElyas, 2003). Growth of nonseptated microhyphae and tubular club shaped macrohyphae resembled that of Kocan et al (2004). The recorded histopathological changes in gas bladder of naturally infected O.niloticus were sloughing in the epithelial layer, subepithelial edema with mononuclear cells infiltration in the submucosa and congestion in the blood vessels of the submucosa with eosinophilic granular cells infiltrations.…”
Section: Discussionmentioning
confidence: 95%
“…This result is in agreement with Mai et al (2005) who recorded that the effectiveness of Mirazid in treatment of fish parasites. In case of I.hoferi infection, (McVicar, 1999 andKocan, et al 2004) suggested that no results of chemotherapy but efforts should be focused on disease prevention. According to the present study, invitro sensitivity test of isolated bacterial strains to different chemotherapeutic agents revealed that all isolates were sensitive to oxytetracycline while vary in susceptibility to the other chemotherapeutic agents (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, no incidence of Ichthyophonus infection was reported until the late 1990s, when the infection became widely noticeable throughout the river drainage. The source of Ichthyo phnus infection for Yukon River Chinook salmon is un known, but it is believed that infection occurs in the ocean prior to freshwater migration through ingestion of infected prey (Criscione et al 2002, Jones & Dawe 2002, Kocan et al 2004a. Ichthyo phonus primarily infects cardiac muscles but spreads throughout the body of a host, which reduces swimming performance and stamina of the host, and leads to its mortality (Tierney & Farrell 2004, Kocan et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Ichthyo phonus primarily infects cardiac muscles but spreads throughout the body of a host, which reduces swimming performance and stamina of the host, and leads to its mortality (Tierney & Farrell 2004, Kocan et al 2006. During the period 1999 to 2003, Ichthyo phonus infection prevalence in the Yukon River was about 25% at the river mouth, peaked at 35% in mid-river, and was about 10% at the spawning grounds (Kocan et al 2004a). This decline from mid-river to spawning grounds was attributed to mortality of the infected fish, in which about 60% of the infected fish die en route to the spawning grounds (Kocan et al 2004a).…”
Section: Introductionmentioning
confidence: 99%